Análisis de las interacciones tróficas en microcosmos: estudio preliminar - Ruiz, Gonzalo Carlos (2008)
The aim of the study was to analyze the effect of planktivorous fish on the trophic interactions between a palatable algae and a filter feeding (Daphnia spinulata). A lab experiment was performed using microcosms of 2 l. Three treatments were carried out: with fishes (P), with cladocerans (C), with fishes and cladocerans (CP) and a control (A). They were inoculated with 200 ml of Scenedesmus acutus. The experiment lasted 5 days and samples were taken every 8 hours. Microcosms were kept at a 16:8 hours of light:dark cycle with constant temperature and with a non limiting level of nutrients (P and N) for algal development. pH values were constant. Turbidity was used as an indirect means of algal biomass ( r = 0.95; p < 0.05). The clearing effect of D. spinulata was more marked at the end of the experiment, with turbidity dropping down in the treatment without fish (C), and showing significant differences when compared with treatments (P) and (A). Differences in turbidity between (P) and (A) showed a possible recycling of nutrients by the fish. Algal palatability was also evident, because cladoceran populations were tripled in density. In (CP), predation by fish was observed resulting in the absence of Daphnia spinulata at the end of the experiment. In experiments with algal mono specific culture, turbidity could be used as an indirect means of algal biomass because, since its register is immediate, it can be measured repeatedly causing minimal disturbance.